Ksiega raju, czyli Przedziwne zywota opisanie Szmula Aby Aberwo - Manger, Itzik, 1901-1969.; Manger, Itzik, 1901-1969. (Warszawa : Panstwowy Instytut Wydawniczy, 1988)
A story based on an old Jewish legend which states that a person before his birth resides in Paradise or Heaven.
Translation of: Dos buch fun gan-eden.